Aspek Performasi Surah Yâsîn dalam Literatur Hadis - Sawaun Sawaun (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2023)
Surah Yâsîn is one of the most popular and recited among other surah of the Koran. In several communities, there is a ritual called Yâsînan. The Yâsînan ritual is a routine ritual performed by Muslim communities, both individually and in groups. The reading of Surah Yâsîn is also often done in commemorations of someone's death. This activity called a performative reception of Qur’an, especially surah Yâsîn, where qur’anic verses (Yâsîn) are accepted and used as a medium for certain rituals, regardless of its informative meaning. This article examine the performance of the surah Yâsîn which are contained ini hadith literatures, both canonical and non-canonical, that appeared up to the fifth century of the hijriah. From this research, there are several forms of performance related to surah Yâsîn. First, surah Yâsîn is recited at the death ritual. Second, surah Yâsîn also recited at certain times. Third, Surah Yâsîn is considered to be the heart of the Qur'an, so reading surah Yâsîn has a quality equivalent to reading the Qur'an several times. Fourth, surah Yâsîn is often used as a medicine for psychic ailments. And fifth, there is a recommendation for reading Yâsîn in certain prayer rituals.